Are professional investors sophisticated? - Lukas Menkhoff; Maik Schmeling; Ulrich Schmidt (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2008)
Existing empirical evidence is inconclusive on whether professional investors show sophisticated behavior or not, a question which is at the heart of market efficiency. This ambiguous evidence is mostly based on trading data or laboratory evidence, which each has its limitations. We complement these approaches by conducting a survey of 500 investors, including several measures of sophistication, three relevant groups of investors and essential control variables. We find that both professional investors and laymen do indeed show unsophisticated investment behavior on aggregate. Furthermore, while some professional investors - institutional investors - behave at least more sophisticated than laymen, other professionals - investment advisors - seem to do even worse.
Keywords: G1; D80; 330; Institutional investors; investment advisors; individual investors; investment behavior; Anlageverhalten; Finanzanalysten; Institutioneller Anleger; Wertpapieranalyse; Deutschland